Systematic client consultation in development: the case of food policy research in Ghana, India, Kenya, and Mali - Babu, Suresh Chandra; Brown, Lynn R.; McClafferty, Bonnie (International Food Policy Research Institute, 1997)
Successful food policy implementation is preceded by a defined policymaking process drawing from a sound information base. Yet too often the knowledge generated through food policy research does not become part of the local body of information and consequently is not used by policymakers. This leads to less than optimal food policies. This paper highlights the need for better linkages to be developed between the food research and food policymaking processes. We propose that a key component of the linkage is the integration of clients into the research process. This paper discusses the link between food policy researchers and one group of clients—food policy decisionmakers. The paper first reviews the role of research and clients in the policymaking process and proposes a conceptual framework that integrates clients into the research process. Case studies utilizing client consultation in Ghana, India, Kenya, and Mali illustrate the hypothesis that integration of all client groups, including policy decisionmakers and in-country researchers, beginning at the priority-setting stage of the research process, may best influence ultimate policy decisions.